(untitled) (Revista NUPEART, 2025)
This text discusses a teaching practice that is permeated by processes of creation and seeks relationships with art by asking: what movements can be triggered by experimenting with different modes of teaching? By presenting some teaching experiences lived at a public university in the south of Brazil (UFSM/RS), it aims to discuss Guided Teaching through the creation of Pedagogical Practice Diaries in the Internship course of the Visual Arts Degree program. The results presented relate to approaches to a teaching formation in becoming, one that embraces different collective processes and problematizes issues regarding teaching and artistic practice.